Ego Strength and It’s Relationship with the Accuracy of Basketball Shooting Performance among the Players of the University of Kirkuk Team - Ibrahim Khorshed (Penerbit Jurnal Indonesia, 2025)
The current study aimed at determining the level of ego strength as well as the accuracy of basketball jump shooting of a sample of basketball players of the Kirkuk University team. In this quest, the study seeks to determine the correlation between these two variables as regards the sampled participants. The methodology used in this study is descriptive with a correlational approach that best suits the nature of the research. The sampled population was assembled in a random fashion from the basketball players at Kirkuk University for the academic year 2024/2025. It was ensured here that the selected participants, who were 14 in total, represent different colleges and departments. Results demonstrated a significant positive relationship between both variables addressed in the current study, i.e. ego strength and shooting accuracy in basketball. This tells us that the role of psychological factors in improving skill performance is of paramount importance. Players with high levels of ego strength were found to displaying greater focus and an improved ability in order to deal with competitive pressures. The study came up with a set of recommendations the main of which is that psychological training programs should be part of the training plans of basketball teams. This is orde enhance players' ego strength and improve their ability to deal with competitive pressures. Moreover, the study could also recommend that players’ concentration skills and self-confidence should be developed using mental strategies such as mental visualization.